Matching Software and Context in Open Learning Scenarios - The Use of Log File Analysis to Evaluate Didactical Fit - Bernd Pape; Monique Janneck; Martin Klein (FernUniversität Hagen, 2005)
We describe the use of log file analysis to investigate whether the use of CSCL applications corresponds to its didactical purposes. Exemplarily we examine the use of the web-based system CommSy as software support for project-oriented university courses. We present two findings: (1) We suggest measures to shape the context of CSCL applications and support their initial and continuous use. (2) We show how log files can be used to analyze how, when and by whom a CSCL system is used and thus help to validate further empirical findings. However, log file analyses can only be interpreted reasonably when additional data concerning the context of use is available.